2009
DOI: 10.12693/aphyspola.116.84
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe2+(Fe3+) Doping on Structural Properties οf CeO2Nanocrystals

Abstract: We have measured the Raman scattering and magnetization of pure and Fe 2+ (Fe 3+ ) doped CeO2 nanopowders at room temperature. The Raman scattering spectra revealed the existence of CeO2 fluorite cubic structure for all investigated samples. The Raman active mode at about 600 cm −1 , seen in all samples, can be ascribed to the CeO2 intrinsic oxygen vacancies. Additional Raman modes at 720 cm −1 , 1320 cm −1 and 1600 cm −1 , which appear in the spectra of doped samples, can be assigned to maghemite (γ-Fe2O3) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is also emphasized that an increase of Ce dopant produces higher disorder in nickel and cobalt structure due to increased oxygen vacancy and metal interstitials which was already confirmed from the PL study. It was suggested that the existence of Ce 3+ –oxygen vacancy with Ni 2+ and Co 3+ ions contributed to the weak ferromagnetic behavior of NiO and Co 3 O 4 samples. …”
Section: Resultsmentioning
confidence: 99%
“…It is also emphasized that an increase of Ce dopant produces higher disorder in nickel and cobalt structure due to increased oxygen vacancy and metal interstitials which was already confirmed from the PL study. It was suggested that the existence of Ce 3+ –oxygen vacancy with Ni 2+ and Co 3+ ions contributed to the weak ferromagnetic behavior of NiO and Co 3 O 4 samples. …”
Section: Resultsmentioning
confidence: 99%
“…Starting materials were metal nitrates and sodium hydroxide. The details of the sample preparation procedure can be found in our recent publications [20,21]. The particle size of the samples under consideration, according to the x-ray diffraction (XRD) and Raman scattering measurements, was less than 5 nm [19].…”
Section: Methodsmentioning
confidence: 99%
“…The interactions between the spin moments of Ce 3+ and oxygen vacancy arise in accordance with F-centered exchange leading to the ferromagnetic character. 38,39 Saturation magnetization for EFCR (5.37 Â 10 À3 ) was found to be higher than that of pure CeO 2 (6.56 Â 10 À4 ). An increase in defect concentration has been observed on co-doping iron and europium as supported by our Raman spectra.…”
Section: Magnetic Propertiesmentioning
confidence: 84%